HISTORICAL AND THEOLOGICAL DIMENSIONS OF THE GOTILON FEAST IN THE HKBP TRADITION - Nainggolan, Alon Mandimpu; Sihombing, Warseto Freddy; Tumba, Patresia R. (Penamas, 2025)
The gotilon feast is an ancient tradition that has been observed both before and after the introduction of Christianity and has undergone a transformation in meaning after being incorporated into the church liturgy in the HKBP Manado. This research aims to analyze the gotilon feast in the context of the Toba Batak diaspora in Manado by examining how this practice is carried out in HKBP Manado as a space for an encounter between religious identity and Toba Batak cultural expression. Using a light qualitative-ethnographic approach, as well as Pierre Bourdieu's theoretical framework - specifically the concepts of habitus, field, and doxa; this research shows that this tradition is the result of symbolic practices that are continuously reproduced, not solely because of theological dogma, but as a result of the social and historical structures that shape it. Within the diasporic social field, the gotilon feast occupies a strategic position as a mechanism for maintaining collective identity. However, it also presents a tension between religious particularism and culture and the demands of multiculturalism within the church. As a spiritual and social glue, this practice makes an important contribution to the conceptualization of contextual theology, the sociology of religion, and the dynamics of Toba Batak diaspora traditional practices.